Representation Of Women In The Novel Rara Mendut By Y.B. Mangunwijaya: A Study Of Liberal Feminism - Astriyani, Astriyani; Wanda Ayu Salsabila; Ilmiyanti Rahayu Putri (Universitas Swadaya Gunung Jati, 2025)
Literary works can be a means of understanding the problems andchallenges of life. Through the novel Rara Mendut, readers canrecognize the problems faced by women as inferiors in society. Thisstudy aims to describe the representation of women in the novel RaraMendut by Y.B. Mangunwijaya and to determine the forms of liberalfeminism in the novel. This research is a qualitative descriptive studyusing the novel Rara Mendut by Y.B. Mangunwijaya as the datasource. This study used reading and note-taking techniques to collectdata. The results of this study indicate that there are representationsof Javanese women in the characters of Rara Mendut, Ni Semangka,Nyai Ajeng, and Putri Arumardi. In addition, this study also foundforms of liberal feminism in the character of Rara Mendut in the novelRara Mendut by Y.B. Mangunwijaya.